Exploring Social Skills and Character Education of Students Through Storytelling in L2 (GIST – Education and Learning Research Journal, 2018)
Little is known about character education and social skills within a transformative curriculum framework in the L2 classroom. This action research study stems from identifying peer rejection in 7th grade English language classrooms as a social issue hampering English language practices for some students. Four L2 storytelling workshops were designed and implemented adapting social and linguistic contents. Data comprising students’ reactions to the content of the adapted short stories were collected using classroom interaction transcriptions, students’ artifacts, field notes, semi-structured interviews with students, and the evaluation of the storytelling workshops made by the students. Data analysis demonstrates that students could learn to live in a community creating healthy L2 learning environments when there is a sense of awareness about accepting differences whilst practicing the use of the English language.
Keywords: social relationships; social skills; L2 storytelling